If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 4w + 4)(5x + -3w) = 0 Reorder the terms: (4 + 4w + 7x)(5x + -3w) = 0 Reorder the terms: (4 + 4w + 7x)(-3w + 5x) = 0 Multiply (4 + 4w + 7x) * (-3w + 5x) (4(-3w + 5x) + 4w * (-3w + 5x) + 7x * (-3w + 5x)) = 0 ((-3w * 4 + 5x * 4) + 4w * (-3w + 5x) + 7x * (-3w + 5x)) = 0 ((-12w + 20x) + 4w * (-3w + 5x) + 7x * (-3w + 5x)) = 0 (-12w + 20x + (-3w * 4w + 5x * 4w) + 7x * (-3w + 5x)) = 0 Reorder the terms: (-12w + 20x + (20wx + -12w2) + 7x * (-3w + 5x)) = 0 (-12w + 20x + (20wx + -12w2) + 7x * (-3w + 5x)) = 0 (-12w + 20x + 20wx + -12w2 + (-3w * 7x + 5x * 7x)) = 0 (-12w + 20x + 20wx + -12w2 + (-21wx + 35x2)) = 0 Reorder the terms: (-12w + 20wx + -21wx + -12w2 + 20x + 35x2) = 0 Combine like terms: 20wx + -21wx = -1wx (-12w + -1wx + -12w2 + 20x + 35x2) = 0 Solving -12w + -1wx + -12w2 + 20x + 35x2 = 0 Solving for variable 'w'. The solution to this equation could not be determined.
| 1+2x/7+3-x/3=46/21 | | 7(x+8)=5x+44 | | -3(8p+2)-2(3-23p)=3(6+7p) | | (1-q)(1-q)=0 | | (1+q)(1+q)=0 | | 6=a/7 | | (29b-1)-7(4b+1)=-5 | | -f+5w+8= | | 5u-8/7=47/9 | | 49-9u-4/2 | | 5u-8/7=49-9u-4/2 | | x+3/5=40 | | 7/5x-4=-2/3x+6/5 | | -7/5w+1/3=-2/5w-2 | | -5/2u-7/2=4u+3/5 | | 8=-64 | | 4(2x-1)-(4x-3)=10 | | 4u-2/5=-4/5u-4/3 | | 5(1/2*y-3)-y=9 | | 3.5x+1.2=3.7-2.5x+3.7 | | (9x+8)(9x+3)= | | -1/2x-1/3=-4/5 | | (x-1)+2=2(x-3)+4x | | x=-5y^2 | | 3/2y-3=9 | | -1/3=6/5v-3/2 | | 5.7q-3.2-5.6q=-0.9q-5.1 | | 6+8x-4=2x+5-3 | | 4x+3y=380 | | 2x-1+x=4x-3 | | 4x-3y=380 | | 2X^2-56X-176=0 |